Analysis of Mobile JKN Application Service Quality With E-GovQual Method and IPA - Ananda, Randy Rizki; Hapsari, Indriani Noor (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
This study aims to evaluate the quality of Mobile JKN application services using 6 dimensions of E-GovQual, and provide recommendations for improving service quality based on the results of Importance Performance Analysis (IPA) analysis. This research uses a quantitative descriptive method. Questionnaires were distributed by visiting BPJS Kesehatan Tigaraksa Branch Office and Metro Hospitals Cikupa. Then, 110 respondents were obtained who had filled out the questionnaire online via Google Forms and were included in the category of Mobile JKN application users. The questionnaire instrument test was conducted on 55 respondents to test its validity and reliability. Data processing was carried out by conducting descriptive statistical tests, R-Square tests, hypothesis tests (significant), as well as gap analysis (GAP) and Importance Performance Analysis (IPA) quadrants. The results of the coefficient of determination (R-Square) show that overall, the variables of ease of use, reliability, trust, content and appearance, functionality and interaction and citizen support significantly affect service quality by 88.6%. Based on the performance gap value (GAP) and assessment expectations of -0.19, there is a main priority scale in quadrant A to make improvements, namely on the information displayed in the Mobile JKN application is precise and detailed (EF 4), all features in the Mobile JKN application function properly (FI 1), the Mobile JKN application has displayed all the information needed by users (CA 1), information about the scope of health and information has provided clarity (CA 2), the accuracy of the summary of information data and graphics and colors in the system (CA 5), and BPJS Kesehatan staff show a responsive attitude in solving my problem (CS 1). These recommendations are top priorities for improving the service quality of the Mobile JKN application.